CLINICAL CHARACTERISTICS OF IDIOPATHIC FOVEOMACULAR RETINOSCHISIS. Issue 8 (August 2016) - Maruko, Ichiro; Morizane, Yuki; Kimura, Shuhei; Shiode, Yusuke; Hosokawa, Mio; Sekiryu, Tetsuju; Iida, Tomohiro; Shiraga, Fumio
Abstract : Purpose: To describe the clinical features of idiopathic foveomacular retinoschisis not in association with myopia, glaucoma, optic disk pit, or juvenile retinoschisis. Methods: Retrospective observational case series. Five eyes of five patients with idiopathic foveomacular retinoschisis were included. Results: The patients were 2 men and 3 women (average age, 75.2 years; range, 71–78 years). The average spherical equivalent was +2.40 diopters (range, +0.88 to +5.75 diopters), and the average axial length was 22.0 mm (range, 21.1–23.1 mm). All patients had retinoschisis from the macula to the optic disk in the affected eye. No patients had retinoschisis in the fellow eye. The average best-corrected visual acuity was 20/44 (68 Early Treatment Diabetic Retinopathy Study letter score). Conclusion: Idiopathic foveomacular retinoschisis is not inherited or associated with myopia, vitreomacular traction syndrome, optic pit, or glaucoma but is associated with older age, unilaterality, hyperopia with short axial length, complete posterior vitreous detachment, and weak leakage from the optic disk on fluorescein angiography. Abstract : Idiopathic foveomacular retinoschisis, which is not inherited or associated with myopia, vitreomacular traction syndrome, optic pit, or glaucoma, is associated with older age, unilaterality, hyperopia with short axial length, complete posterior vitreous detachment, and weak leakage from the optic disk. Vitrectomy with internal limiting membrane peeling is effective for morphologic and visual improvements.